(untitled) (Perner’s Contacts, 2019)
The vast coastline and access to the sea offer wide opportunities for port development in Croatia. During a long and often difficult history, many ports have been created on the coast of this beautiful country and today they play an important role not only in the economy of the Republic of Croatia but also in the lives of its inhabitants. The most important ports include the ports of Rijeka, Zadar, Šibenik Split, Ploče and Dubrovnik. Each of them is unique and original and together they form a developed transport system.